Tubular membrane electrode assembly for PEM electrolysis. (29th April 2022) - Laube, A.; Hofer, A.; Sánchez Batalla, B.; Ressel, S.; Chica, A.; Fischer, S.; Weidlich, C.; Bachmann, J.; Struckmann, T.
Abstract: Polymer electrolyte membrane (PEM) water electrolysis is already widely used for hydrogen production but still needs further cost reductions. While tubular cell designs might reduce production costs by extrusion production of cell components and small sealing lengths, catalyst coating methods like atomic layer deposition (ALD) might reduce catalyst costs significantly. This study demonstrates the feasibility of a tubular PEM electrolyzer membrane electrode assembly (MEA) for the oxygen half cell with 5.0 mm diameter. An extruded perfluorosulfonic acid (PFSA) cation exchange membrane is combined with a porous transport electrode (PTE) consisting of a titanium felt with a low iridium catalyst loading obtained by ALD. The performance is experimentally characterized in a complete tubular cell setup by polarization curve and ohmic resistance measurements. Operation in sulphuric acid at a cell voltage of 1.7 V and a cell temperature of 60 ° C results in an overall current density of 55 mA cm −1 and an iridium mass activity > 680 A g −1 which is up to 3 times larger than literature values. The high frequency ohmic resistance of the cell turns out to be 0.96 Ω cm −2 . Up to the knowledge of the authors, this is the first time, that a tubular PEM electrolysis cell is designed, assembled and characterized. Highlights: Tubular membrane electrode assembly suitable for in-line co extrusion. Utilisation of porous transport electrodes with low catalyst loading by atom layer deposition. Characterization of a tubular PEM electrolysis cell.